DISTAL SPINAL MUSCULAR ATROPHY WITH VOCAL PARESIS: FROM THE WELSH CHOIR TO GENES. Issue 11 (9th October 2013) - Ingram, Gillian; Barwick, Katy; McEntagart, Meriel; Crosby, Andrew; Hartley, Louise; Llewelyn, Gareth; Morris, Huw
Abstract : Distal spinal muscular atrophy (SMA) represents approximately 10% of the peroneal muscular atrophy syndromes, differing from demyelinating and axonal hereditary sensory motor neuropathy (HSMN) in the preservation of normal motor and sensory nerve conduction velocities but neurogenic atrophy on electromyography indicating anterior horn cell dysfunction. Phenotypic features and prognosis in distal SMA are variable and clinical and genetic criteria have been used to define seven disease subtypes. Autosomal dominant distal SMA with vocal paresis (distal hereditary motor neuronopathy type 7–DHMN7) has been described in two unrelated families both from Wales. Genetic analysis from affected families has shown linkage to chromosome 2q14. More recent linkage analysis and whole exome sequencing has identified a pathogenic frameshift mutation in SLC5A7 in one family, which encodes the presynaptic choline transporter involved in synaptic acetylecholine synthesis at the neuromuscular junction1. Although two further families from France and Swizerland have been described with a similar phenotype to DHMN7, they have clinical differences, one case describing more proximal involvement and the other family showing associated hearing loss. A congenital form of DHMN with vocal paresis affecting only lower limbs has been described in multiple families due to mutation of the TRPV4 gene at chromosome 12q24.112. We describe a further family with DHMN and vocal paresis in a mother and daughter. Both patients, in their early teenage years were keen singers, competing in Eisteddfodau. The predominant presenting feature in both cases was a change in the quality of voice in the late teenage years, particularly noticeable when singing. In the mother this has been demonstrated to be due to a persistent glottic chink allowing air to escape through the vocal cords during speech. In both patients the neuronopathy predominantly affects the upper limbs with early involvement of the median nerve innervated muscles, progressing in later stages to involve the lower limbs to a lesser degree; the proband is mobile independently at the age of 49 years. Electrophysiology in both is consistent with spinal muscular atrophy showing normal motor and sensory nerve conduction velocities. Genetic analysis in the proband has identified the pathogenic c.1497delG mutation in the SLC5A7 gene, which leads to a frameshift and premature truncation of the presynaptic choline transporter. We draw attention to this rare from of neuronopathy which has now been identified in three apparently unrelated families in Wales. The clinical presentation of this family is characteristic and we have identified the common truncating mutation in the SLC5A7 gene. Advances in genetic anaylsis of these rare conditions broadens our understating of the potential molecular lesion and may allow more directed therapy.